On Whales and Giants: Images of Leviathan in New Model Army and The Unwritten (Gragoatá, 2017)
Fantastic and science-fictional narratives employ specific modes of representation. In both genres, figurative language can be used in a literal sense, so that symbols acquire a concrete representation in the text. The aim of this article is to examine how a specific image, the giant Leviathan as a metaphor for the aggregation of individuals in order to form the social body, is explored in two genre narratives. In the science fiction novel New Model Army, by Adam Roberts, the image of Thomas Hobbes’ Leviathan is used to suggest the notion of a radical democracy in which all members of the community have an organic participation in the social body. In the graphic narrative The Unwritten, by Mike Carey, Peter Gross and Vince Locke, Hobbes’ Leviathan is explored in conjunction with Melville’s Moby-Dick in order to investigate the nature of symbolic representation and the relation between culture and objective reality. The appropriation of the metaphor of the Leviathan as a concrete symbol determines the way the two narratives develop their main themes and articulate their meanings.---------------------------------------------------------------------------------SOBRE BALEIAS E GIGANTES: IMAGENS DO LEVIATÃ EM NEW MODEL ARMY E THE UNWRITTENNarrativas fantásticas e de ficção científica empregam modalidades de representação específicas. Em ambos os gêneros, a linguagem figurada pode ser empregada num sentido literal, de modo que os símbolos adquiram uma representação concreta no texto. O objetivo deste artigo é examinar como uma imagem específica, a do gigante Leviatã como uma metáfora da agregação dos indivíduos para formar o corpo social, é explorada por uma narrativa fantástica e outra de ficção científica. No romance de ficção científica New Model Army, de Adam Roberts, a imagem do Leviatã de Hobbes é usada para propor a noção de uma democracia radical em que todos os membros da comunidade têm uma participação orgânica no corpo social. Na narrativa gráfica The Unwritten, de Mike Carey, Peter Gross e Vince Locke, o Leviatã de Hobbes é explorado em conjunto com o Moby-Dick de Melville para investigar a natureza da representação simbólica e a relação entre cultura e realidade objetiva. A apropriação da metáfora do Leviatã como símbolo concreto determina a maneira como as duas narrativas desenvolvem os seus temas principais e articulam os seus significados.---Artigo em inglês. ---DOI: http://dx.doi.org/10.22409/gragoata.2017n43a943.